Evaluation of rations with different levels of fibre for sheep - Arruda, Francisco de Assis V.; Souza, Antonio Alves de; Johnson, William L.; Pant, Kant P. (Pesquisa Agropecuaria Brasileira, 2014)
Twelve castracted and mature rams of Morada Nova breed were used in a 3 x 2 factorial experiment to study 3 rations containing 60, 70 and 80% of corn crop residue and 23, 13 and 3% corn meal respectively in two different periods. In the second period, animals were rotated among treaments. All rations contained 17% of cottonseed meal, about 9.2% of crude protein in dry matter and were isonitrogenous. There were no significant differences between rations (P>0.05) in digestibilities of dry matter, crude protein, nitrogen-free extract and total digestible nutrients. Differences between rations (P<0.05) were observed in digestibilities of crude fibre, crude energy and ether extract. The digestibility of crude fibre and crude energy declined when corn crop residue was increased from 60 to 70% and remained at that low level at 80%. The digestibility of ether extract exhibited a marked decline when corn crop residue was increased from 70 to 80%. A marginal reduction in the consumption of dry matter was observed with increase in the proportion of corn crop residue, but was not significant (P>0.05).